Didáctica de las lenguas extranjeras : paradigmas de investigación - Vez, José Manuel (Linguarum Arena, 2018)
In this paper the main goal is to contribute to a thoughtful analysis and discussion of findings from my own and others’ work on past and present concerns raised over the contextual factors influencing language education research and, more specifically, what is known as “foreign language” research. The most obvious outcome emerging from this discussion shows that foreign language education, when seen from the perspective of foreign language learning, teaching and evaluation, has evolved in a dynamic way in the last decades. This dynamism tightly parallels the convoluted ideas forged, at least in the European context, by the social, cultural and political changes about the nature of human beings themselves and what their general and specific competences are.